Female vs. Male Ampelmännchen-Gender-Specific Reaction Times to Male and Female Traffic Light Figures - Kandil, Farid I.; Olk, Bettina; Hilgetag, Claus C. (Frontiers in Psychology, 2017)
Traffic signs are important visual guiding signals for the safe navigation through complex road traffic. Interestingly, there is little variation in the traffic signs for cars around the world. However, remarkable variation exists for pedestrian traffic signs. Following up from an earlier study, we investigated the visual efficacy of female versus male German Ampelmännchen pedestrian traffic signs. In a Stroop-like test, 30 subjects were presented with female and male go and no-go traffic light figures that were shown either in the corresponding or opposing colour. Subjects had to indicate based either solely on the form or the colour of the figure whether they were allowed to go. Accuracy and response time across all subjects did not differ for the female versus male signs, indicating that Ampelfrau and Ampelmann signs have equal visual efficacy. Next to that, subjects responded faster to signs of their own vs the opposite gender. This preference for signs of one's own gender is in accordance with effects in social psychology described by the social learning theory. An introduction of these new traffic lights may thus contribute to a higher compliance by identification to the directions presented by the traffic lights and may possibly even contribute to reducing the amount of jaywalkers.